2007
DOI: 10.1002/jso.20747
|View full text |Cite
|
Sign up to set email alerts
|

Anus‐preservation treatment for anal cancer: Retrospective analysis at a single institution

Abstract: With careful monitoring of toxicity, non-surgical anus-preservation treatment with good tumor control is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, some studies claiming to demonstrate a QoL impact of anal cancer treatment have done so with inappropriate QoL measures, for example, one comparison of QoL following radiochemotherapy and surgery was based on data extracted from medical records [50] which will give a very incomplete assessment. Generic cancer QoL measures such as the EORTC QLQ-C30 are designed to capture issues relevant to all cancer types but are insensitive to unique disease-related features.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies claiming to demonstrate a QoL impact of anal cancer treatment have done so with inappropriate QoL measures, for example, one comparison of QoL following radiochemotherapy and surgery was based on data extracted from medical records [50] which will give a very incomplete assessment. Generic cancer QoL measures such as the EORTC QLQ-C30 are designed to capture issues relevant to all cancer types but are insensitive to unique disease-related features.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the performance status was an independent predictor for OS 17,28,29. Martenson, et al17 reported that patients with a good performance status had much better 5-year OS as compared to that of the patients with a poor performance status (74% vs. 55%, respectively; p =0.045).…”
Section: Discussionmentioning
confidence: 55%
“…Martenson, et al17 reported that patients with a good performance status had much better 5-year OS as compared to that of the patients with a poor performance status (74% vs. 55%, respectively; p =0.045). Moreover, Chen, et al29 showed that the performance status was a significant prognostic factor for OS ( p <0.001).…”
Section: Discussionmentioning
confidence: 99%